Critical Perspectives in Speech-Language Therapy: Towards Inclusive and Empowering Language Practices - Geneviève Lamoureux; Alexandra Tessier; Sébastien Finlay; Ingrid Verduyckt (Disabilities)
This conceptual paper critically examines the use of traditional medicalized terminology in speech-language therapy, with a particular focus on the Quebec context. It highlights how current language practices, rooted in a medical model of disability, often marginalize individuals with communication differences such as stuttering, autism, and aphasia by pathologizing these variations. Drawing on contemporary frameworks such as the social model of disability, neurodiversity, and “diversité capacitaire” (a French term that translates to “capacity diversity” or “ability diversity”, emphasizing the richness of diverse abilities and communication styles), the article advocates for more inclusive and empowering language that respects and reflects communicative diversity. The authors emphasize the importance of participatory approaches, including consultation with the communities directly involved and the establishment of terminological committees, to develop respectful and affirming language. Ultimately, this paper calls for a shift in speech-language therapy practices to promote a more inclusive understanding of communication, enabling individuals with communication differences to fully participate in society.